2019
DOI: 10.1016/j.jdsr.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

B cell dysregulation in primary Sjögren’s syndrome: A review

Abstract: Primary Sjögren’s syndrome is a chronic autoimmune disorder of unknown etiology and is characterized by progressive focal lymphocytic infiltration of the lacrimal and salivary glands. Comparison of B cell subsets from the peripheral blood and salivary glands of patients with primary Sjögren’s syndrome and those from healthy individuals shows dysregulation and derangement of B cell subsets in both peripheral circulation and in inflamed glandular tissues. This dysregulation is expressed as a decrease in the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 90 publications
3
25
0
Order By: Relevance
“…Two chemokines involved in the attraction of T-cells in SS SG are CXCL9 and CXCL10 [ 123 ]. In SS SG, T cells are likely to be involved in the disruption of the glandular architecture throughout the apoptosis mechanism mediated by FasL pathway [ 124 ], by a direct cytotoxic activity involving the release of perforin and/or secretion of cytokines and by the activation of B cells [ 125 ]. Th17 cells represent another subpopulation of T-cells strongly activated in SS patients [ 126 ].…”
Section: Physiopathology Of Sjögren’s Syndromementioning
confidence: 99%
“…Two chemokines involved in the attraction of T-cells in SS SG are CXCL9 and CXCL10 [ 123 ]. In SS SG, T cells are likely to be involved in the disruption of the glandular architecture throughout the apoptosis mechanism mediated by FasL pathway [ 124 ], by a direct cytotoxic activity involving the release of perforin and/or secretion of cytokines and by the activation of B cells [ 125 ]. Th17 cells represent another subpopulation of T-cells strongly activated in SS patients [ 126 ].…”
Section: Physiopathology Of Sjögren’s Syndromementioning
confidence: 99%
“…It was previously concluded that B cell dysregulation occur in the pSS with the decrease in the percentage of CD27+ memory B cells in peripheral blood and an increase in the CD27+ memory B cells in the affected glands (31). B lymphocytes, by their nature, generally exhibit increased activation states in pSS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both SS and CD pathologies are associated with an increased risk of lymphoma occurrence. Initially considered a T cell dysregulation, we recognized that the major derangement and dysregulation of the B lymphocytes in both peripheral circulation and glandular tissues of the SS patients plays a central part in the pathogenic processes[ 44 ]. The lymphoma risk is increased in SS patients especially for the marginal zone lymphoma, namely the parotid gland mucosa associated lymphoid tissue lymphoma, and the diffuse large B-cell lymphoma[ 45 ].…”
Section: Discussionmentioning
confidence: 99%